Investigation of optical attenuation imaging using optical coherence tomography for monitoring of scars undergoing fractional laser treatment. Issue 4 (31st May 2016) - Es'haghian, Shaghayegh; Gong, Peijun; Chin, Lixin; Harms, Karl‐Anton; Murray, Alexandra; Rea, Suzanne; Kennedy, Brendan F.; Wood, Fiona M.; Sampson, David D.; McLaughlin, Robert A.
Abstract : We demonstrate the use of the near‐infrared attenuation coefficient, measured using optical coherence tomography (OCT), in longitudinal assessment of hypertrophic burn scars undergoing fractional laser treatment. The measurement method incorporates blood vessel detection by speckle decorrelation and masking, and a robust regression estimator to produce 2D en face parametric images of the attenuation coefficient of the dermis. Through reliable co‐location of the field of view across pre‐ and post‐treatment imaging sessions, the study was able to quantify changes in the attenuation coefficient of the dermis over a period of ∼20 weeks in seven patients. Minimal variation was observed in the mean attenuation coefficient of normal skin and control (untreated) mature scars, as expected. However, a significant decrease (13 ± 5%, mean ± standard deviation) was observed in the treated mature scars, resulting in a greater distinction from normal skin in response to localized damage from the laser treatment. By contrast, we observed an increase in the mean attenuation coefficient of treated (31 ± 27%) and control (27 ± 20%) immature scars, with numerical values incrementally approaching normal skin as the healing progressed. This pilot study supports conducting a more extensive investigation of OCT attenuation imaging for quantitative longitudinal monitoring of scars.En face 2D OCT attenuation coefficient map of a treated immature scar derived from the pre‐treatment (top) and the post‐treatment (bottom) scans. (Vasculature (black) is masked out.) The scale bars are 0.5 mm. Abstract : This study uses optical coherence tomography (OCT) to longitudinally quantify the non‐vascular changes in the dermis of skin burn scars over a period of ∼20 weeks, using OCT attenuation coefficient. Changes in scars due to ablative fractional laser treatment are identified and compared to untreated scars and normal skin of seven patients. This pilot study supports more extensive investigation of OCT attenuation imaging for quantitative longitudinal monitoring of scars.